2006
DOI: 10.1200/jco.2005.04.0352
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Single Compared With Tandem High-Dose Chemotherapy Followed by Autologous Stem-Cell Transplantation in Patients With Chemotherapy-Sensitive Metastatic Breast Cancer

Abstract: Despite a trend of improved progression-free survival, tandem HDT cannot be recommended for patients with chemotherapy-sensitive metastatic breast cancer because of a trend for shorter overall survival and higher toxicity compared with single HDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Whether patients that receive tandem autologous HPCTs for malignancies other than myeloma are at increased risk for the development of autologous GVHD is not known, although, to date, this complication has not been reported to be increased in these patient populations. [34][35][36][37] In conclusion, this study demonstrates that severe steroid-refractory GVHD can occur after autologous HPCT for multiple myeloma. The incidence of this complication appears to be much higher in patients receiving second HPCTs suggesting that the repetitive exposure to high-dose chemotherapy may compromise reconstitution of regulatory networks that are necessary for the maintenance of self-tolerance.…”
Section: Discussionmentioning
confidence: 54%
“…Whether patients that receive tandem autologous HPCTs for malignancies other than myeloma are at increased risk for the development of autologous GVHD is not known, although, to date, this complication has not been reported to be increased in these patient populations. [34][35][36][37] In conclusion, this study demonstrates that severe steroid-refractory GVHD can occur after autologous HPCT for multiple myeloma. The incidence of this complication appears to be much higher in patients receiving second HPCTs suggesting that the repetitive exposure to high-dose chemotherapy may compromise reconstitution of regulatory networks that are necessary for the maintenance of self-tolerance.…”
Section: Discussionmentioning
confidence: 54%
“…In conclusion, due to the severe toxicity of HDC and the absence of a proven benefit, the final recommendation was to avoid the high-dose strategy outside of clinical trials (28). The recent randomized trials also confirmed, in unselected patient populations, the lack of a benefit from HDC either up front or as consolidation after response to standard induction chemotherapy (2935). …”
Section: The Role Of Systemic Treatmentmentioning
confidence: 82%
“…Data flow is shown in Figure 1 and study data is presented in Appendix 1. Two articles represented data from the same clinical trial Slamon et al, 2001), and three of the 71 abstracted articles were subsequently excluded because they used high-dose chemotherapy, which has limited application to current clinical practise (Lotz et al, 2005;Schmid et al, 2005;Kröger et al, 2006). The resulting 67 clinical trials represent 17 081 patients.…”
Section: Resultsmentioning
confidence: 99%